Variabilidade do albedo planetário na América do Sul - Santos, Wially Roger Tavares (2015)
The Climate Dynamics has its origin due to radiant energy emitted by the sun. This radiated energy interacting with the Earth's surface results in ocean-land-atmosphere interactions. The ENSO (El Niño - Southem Oscilacion) is a phenomenon resulting from ocean-atmosphere interaction, it is considered a climate forcing, because it reduces or accelerates the circulation cooling or warming the planet. The planetary albedo plays a key role in maintaining the climate balance and has clouds factor as the main and most complex component for understanding climate dynamics. The CERES (Clouds and the Earth’s Radiant Energy System) is a project devoted to evaluating the properties of clouds as well as through mapping, find answers about their influence on the climate. This study aims at evaluating the oscillation of the planetary albedo to South America in times of El Niño and La Niña, correlating it with the MEI (Multivariate Enso Index) and the SOI (Southem Oscilacion Index). Results for exploratory data analysis show a great diversity in the values of the planetary albedo of all regions studied during the year and especially for regions where El Niño and La Niña are influenced. The albedo of correlations with indicators of ENSO indices show a better correlation when you anticipate in a month. For analysis with wavelet the results indicate common condition seasonality and conditions of ENSO. As for principal component analysis the result shows an indirect relationship between the central region and further south, suggesting a normal condition to atmospheric circulation patterns.